Role of hepatic blood flow and metabolism in the pharmacokinetics of ten drugs in lean, aged and obese rats. (December 2014) - Subramanian, Murali; Kurawattimath, Vishwanath; Pocha, Krishna; Freeden, Chris; Rao, Indranil; Thanga Mariappan, T.; Marathe, Punit H.; Vikramadithyan, Reeba K.; Abraham, Pamela; Kulkarni, Chetan P.; Katnapally, Prasanna; Nutakki, Ravikumar; et al.
Abstract 1. The effect of age and obesity on the pharmacokinetics (PK), hepatic blood flow (HBF) and liver metabolism of 10 compounds was determined in rats. The animals fed a high-fat diet were defined as the diet-induced obese (DIO) group, while the animals that were aged similar to the DIO rats but not fed with high-fat diet were called the age-matched (AM) group. 2. The clearance (CL) values of high CL compounds (CL > 50 mL/min/kg, namely propranolol, diazepam, phenytoin, ethinylestradiol, lorcaserin and fenfluramine) decreased significantly (1.5- to 6-fold) in DIO and AM rats as compared to lean rats, while there was no clear trend for change in CL for the low-to-moderate CL compounds (CL < 50 mL/min/kg, namely atenolol, chlorzoxazone, vancomycin and sibutramine). Hepatocytes incubations revealed a change in half life (t1/2) only for phenytoin. The body weight normalized liver weights and HBF of AM and DIO rats were found to be 2- to 3-fold lower than in lean rats. 3. Our findings suggest that age, and diet to a lesser extent, can reduce HBF and body normalized liver weights and, hence, also reduce CL values for high CL compounds in rats.